Role of the bed nucleus of the stria terminalis in cardiovascular changes following chronic treatment with cocaine and testosterone: A role beyond drug seeking in addiction? - Cruz, F. C. [UNESP]; Alves, F. H F; Leão, R. M. [UNESP]; Planeta, Cleopatra da Silva [UNESP]; Crestani, Carlos Cesar [UNESP] (Elsevier, 2013)
Neural plasticity has been observed in the bed nucleus of the stria terminalis (BNST) following exposure to both cocaine and androgenic-anabolic steroids. Here we investigated the involvement of the BNST on changes in cardiovascular function and baroreflex activity following either single or combined administration of cocaine and testosterone for 10 consecutive days in rats. Single administration of testosterone increased values of arterial pressure, evoked rest bradycardia and reduced baroreflex-mediated bradycardia. These effects of testosterone were not affected by BNST inactivation caused by local bilateral microinjections of the nonselective synaptic blocker CoCl2. The single administration of cocaine as well as the combined treatment with testosterone and cocaine increased both bradycardiac and tachycardiac responses of the baroreflex. Cocaine-evoked baroreflex changes were totally reversed after BNST inactivation. However, BNST inhibition in animals subjected to combined treatment with cocaine and testosterone reversed only the increase in reflex tachycardia, whereas facilitation of reflex bradycardia was not affected by local BNST treatment with CoCl2. In conclusion, the present study provides the first direct evidence that the BNST play a role in cardiovascular changes associated with drug abuse. Our findings suggest that alterations in cardiovascular function following subchronic exposure to cocaine are mediated by neural plasticity in the BNST. The single treatment with cocaine and the combined administration of testosterone and cocaine had similar effects on baroreflex activity, however the association with testosterone inhibited cocaine-induced changes in the BNST control of reflex bradycardia. Testosterone-induced cardiovascular changes seem to be independent of the BNST. © 2013 IBRO.
Keywords: Addiction; Baroreflex; BNST; Cocaine; Extended amygdala; Steroids